Impact of Toupet Versus Nissen Fundoplication on Dysphagia in Patients With Gastroesophageal Reflux Disease and Associated Preoperative Esophageal Dysmotility: A Systematic Review and Meta-Analysis. (December 2018) - Hajibandeh, Shahin; Hajibandeh, Shahab; Pugh, Merili; Winters, David; Hobbs, Nicholas; Tarazi, Munir; Panda, Nilanjan; Dalmia, Sanjay; Mansour, Moustafa; Malik, Sohail
Background . Controversy exists regarding the best surgical approach for the management of gastroesophageal reflux disease (GORD) and associated preoperative esophageal dysmotility. Our aim was to conduct a systematic review and meta-analysis to compare the outcomes of Toupet fundoplication (TF) and Nissen fundoplication (NF) in patients with GORD and coexistent preoperative esophageal dysmotility. Methods . We conducted a systematic search of electronic information sources, including MEDLINE, EMBASE, CINAHL, CENTRAL, ClinicalTrials.gov, and bibliographic reference lists. We applied a combination of free text search and controlled vocabulary search adapted to thesaurus headings, search operators, and limits in each of the above-mentioned databases. Postoperative dysphagia and improvement in dysphagia were primary outcome parameters. Results . We identified 3 randomized controlled trials and 1 observational study reporting a total of 220 patients, of whom 126 underwent TF and the remaining 94 patients had NF. Despite the existence of significantly higher preoperative dysphagia in the TF group (29.3% vs 4.2%, P = .05), TF was associated with significantly lower postoperative dysphagia (odds ratio [OR] = 0.31, P = .002) with low between-study heterogeneity ( I 2 = 11%, P = .34), and significantly higher improved dysphagia (OR = 10.32, P < .0001) with moderate between-study heterogeneity ( I 2 = 31%, P = .23) compared with NF. Conclusion . TF may be associated with significantly lower postoperative dysphagia than NF in patients with GORD and associated preoperative esophageal dysmotility. However, no definite conclusions can be drawn as the best available evidence comes mainly from a limited number of heterogeneous randomized controlled trials. Future studies are encouraged to include patients with similar preoperative dysphagia status and report the outcomes with respect to recurrence of acid reflux symptoms.